Multi-wavelength Fibril Dynamics and Oscillations above Sunspot-II Wave Propagation Signature - Emanuel Sungging Mumpuni; Dhani Herdiwijaya; Mitra Djamal; Thomas Djamaluddin (Institute for Research and Community Services (LPPM) ITB, 2018)
In this work, the dynamics of one particular fibril were investigated through high-resolution multi-wavelength images with high cadence obtained from the Dutch Open Telescope. Based on exceptional observation data of Active Region 10789, 13th July 2005, we investigated the alternating fibril pattern using tomography of the multi-wavelength band, consisting of the hydrogen alpha line center and also the blue wing, the calcium II H line, and the G-band. Phase difference and coherence analyses were conducted for several points along the fibril and (k, Ï‰) analysis was conducted to understand the wave interaction and its mechanism in the propagation process. Our findings suggest short- to long-period transitions along the fibril with coherence in 10-min oscillations in the penumbra.